A SYSTEMATIC REVIEW OF ERP ADOPTION IN SMALL AND MEDIUM ENTERPRISES: CHALLENGES AND OPPORTUNITIES IN DEVELOPING COUNTRIES - Helmi Roichatul Jannah; Puteri Awaliatush Shofro; Novi Prisma Yunita (Jurnal Teknologi Informasi Mura (JTI), 2025)
Enterprise Resource Planning (ERP) systems have become a critical enabler for organizational integration, efficiency, and digital transformation. However, the adoption of ERP systems among Small and Medium Enterprises (SMEs) in developing countries remains challenging and uneven. This study presents a systematic literature review of 71 peer-reviewed articles to examine the key challenges and opportunities associated with ERP adoption in SMEs within developing country contexts. Following the TOE (Technology Organization Environment) Framework, articles were screened, and analyzed from major academic databases. The synthesis reveals that technological factors (system complexity, compatibility, and data security), organizational factors (top management support, user competence, and resource constraints), and environmental factors (vendor support, regulatory pressure, and competitive intensity) are the dominant determinants influencing ERP adoption. Despite persistent challenges such as high implementation costs, resistance to change, and limited technical expertise, emerging opportunities-particularly cloud-based ERP, modular implementation strategies, and scalable subscription models-offer promising pathways for SMEs. This review contributes by consolidating fragmented empirical findings and identifying research gaps related to sustainability, post-adoption performance, and longitudinal impacts of ERP adoption in developing economies.